2017
DOI: 10.4085/1062-6050-52.7.03
|View full text |Cite
|
Sign up to set email alerts
|

Acute Passive Static Stretching and Cramp Threshold Frequency

Abstract: Acute passive static stretching did not seem to increase the CTF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Therefore, the present study investigated the hypothesis that ingestion of spring water after 2% dehydration induced by DHR in the heat would decrease TF, but no changes in TF would be observed after ingestion of ORS. Previous studies have used TF of the abductor hallucis muscle,13–15 or the plantar flexors,16 and used a decrease in TF as a marker of increased muscle cramp susceptibility. In the present study, a TF measure of calf muscles was established and used to assess muscle cramp susceptibility after DHR in the heat, and OS-1 ® (Otsuka Pharmaceutical Factory, Japan) was used as ORS.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the present study investigated the hypothesis that ingestion of spring water after 2% dehydration induced by DHR in the heat would decrease TF, but no changes in TF would be observed after ingestion of ORS. Previous studies have used TF of the abductor hallucis muscle,13–15 or the plantar flexors,16 and used a decrease in TF as a marker of increased muscle cramp susceptibility. In the present study, a TF measure of calf muscles was established and used to assess muscle cramp susceptibility after DHR in the heat, and OS-1 ® (Otsuka Pharmaceutical Factory, Japan) was used as ORS.…”
Section: Introductionmentioning
confidence: 99%
“…TF has been used to assess muscle cramp susceptibility in the previous studies for the abductor halluces muscle [18,19,23] or the plantar exors [14]. For example, Behringer et al [14] showed that neuromuscular electrical stimulation performed twice a week for 6 weeks reduced the number of spontaneous calf cramps by 78%, and this was accompanied by an increase in the cramp threshold frequency from 15.5 ± 8.5 Hz to 21.7 ± 12.4 Hz.…”
Section: Discussionmentioning
confidence: 99%
“…To quantify muscle cramp susceptibility, previous studies [14][15][16][17][18][19] used electrical stimulation to induce muscle cramp, and showed that muscle cramp was induced by increasing the electrical stilumation frequency, and the threshold frequency that induced muscle cramp could be used as an indicator of muscle cramp susceptibility. Lau et al [16] reported that spring water ingestion after dehydration equivalent to 2% of body mass induced by downhill running in the heat (35-36°C), increased muscle cramp susceptibility assessed by a threshold frequency (TF) of electrical train stimulation to induce cramp.…”
Section: Introductionmentioning
confidence: 99%
“…A review by Nelson and Churilla stated that there is ‘strong evidence’ that passive stretching is the most effective treatment for muscle cramping, but did not identify this evidence [60]. More recently, Panza et al tested the possible association between acute static stretching of the muscle and prevention of cramping, using an experimental model whereby cramp was induced in the flexor hallucis brevis muscle by electrical stimulation with the muscle held in a shortened position [61]. In a crossover study, static stretch was compared with a no-stretch condition; the cramp TF increased in both the control and stretching conditions, with no difference between conditions.…”
Section: Possible Preventive and Treatment Strategiesmentioning
confidence: 99%